THE ROLE OF FINANCIAL RISKS IN ASSESSING AND OPTIMIZING THE IMPACT OF GOVERNMENT SPENDING ON ECONOMIC GROWTH - Khurshidbek Kurbonaliev (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This thesis examines, from a theoretical perspective, how financial risks shape the assessment and optimization of government spending’s effect on economic growth in developing countries. It argues that while public expenditure on infrastructure, health, and education can raise both short-run demand and long-run productive capacity, three financial risks debt sustainability, inflation, and contingent liabilities substantially condition the size and direction of fiscal multipliers. High and growing public debt narrows fiscal space, raises borrowing costs, and can reduce or reverse the growth impact of additional spending. Inflation, whether driven by monetary financing or capacity constraints, erodes the real value and effectiveness of public investment and raises uncertainty for private investors. Contingent liabilities (guarantees, bailouts, PPP commitments) represent hidden fiscal exposures that can abruptly raise public debt and crowd out development spending. The thesis synthesizes theoretical frameworks (Keynesian demand management and endogenous growth models) with institutional guidance from the IMF and World Bank (Debt Sustainability Framework and fiscal-risk best practices), and concludes that optimizing fiscal policy in developing economies requires careful composition of spending, medium-term fiscal frameworks, explicit fiscal risk management, and strong institutions to preserve both growth and macro-financial stability.